Sosialisasi Hukum Pencegahan Perundungan di SMA Negeri 2 Slawi - Moh Taufik; Sugiyanto Sugiyanto; Soesi Idayanti; Evy Indriasari; Sanusi Sanusi; Moh. Wildan (Jurnal Kabar Masyarakat, 2026)
The practice of bullying is an act of exercising dominance to inflict harm upon others through verbal abuse, physical violence, or psychological pressure, which ultimately leaves the victim in a state of depression and chronic helplessness. This concept is derived from the English term "bull," representing an animal that strikes out unpredictably. In an etymological sense, it refers to individuals who target the vulnerable. Perpetrators, known as bullies, operate under the assumption that they possess the power to control their victims, who feel permanently intimidated and weak. The primary goal of this particular initiative is to equip students with a deep awareness regarding the necessity of helping one another and fostering genuine care within their community. Furthermore, it seeks to prevent the occurrence of bullying behaviors, considering that such toxic actions result in detrimental impacts that affect not only the victims and the perpetrators but also the entire social fabric of the institution.